Pemberdayaan Karakter Kristiani Melalui Pembelajaran Interaktif: Implementasi Quizizz Sebagai Media Edukasi di Remaja GBI Pelita Imanuel - Rajiman Andrianus Sirait (Jurnal Silih Asih, 2024)
In the current digital era, understanding the nature of adolescents becomes crucial considering the influence of technology affecting their character development. The formation of identity and life purpose in adolescents is influenced by social environment and the Christian values they adopt. The implementation of Quizizz application in teaching at GBI Pelita Imanuel provides an enjoyable interactive experience for students, yet it also demonstrates some limitations, particularly in character development. Evaluation indicates improvement in subject understanding, but additional activities are still needed to strengthen character aspects. Although Quizizz offers benefits in student interaction and comprehension, it should be noted that Christian religious education involves character aspects not fully accommodated by the interactive quiz format. Therefore, a holistic and diverse approach to teaching is still required to develop deep Christian character in adolescents.